Impact of cold conditions on diesel injection processes of biodiesel blends. (October 2016) - Tinprabath, P.; Hespel, C.; Chanchaona, S.; Foucher, F.
Abstract: In this article, we report experimental results on the impact of cold conditions on diesel and biodiesel blends injection processes. We focus on cold conditions in view of the new Euro VI standards concerning problems related to cold-start. A Bosch CRI 3.1 piezoelectric injector was used on a typical diesel engine. Five fuel types were tested: diesel, winter diesel, diesel–biodiesel blends (B50), a winter diesel-biodiesel blend (B50(W)) and pure biodiesel (B100). Injection pressures of 30–60 MPa were tested (during start-up of the engine) in order to study the injection flow characteristics at room temperature and in cold conditions. Under cold conditions, the discharge coefficients for all fuels were lower than at room temperature. When the fraction of biodiesel in the blend increased, the discharge coefficients decreased slightly. Spray penetration increased and spray angle strongly decreased in cold conditions. This behavior was particularly clear for the B100 fuel. Winter diesel despite a higher viscosity than diesel showed most interesting performance in terms of discharge coefficient both at low temperature than at room temperature. These benefits disappear with the blend with biodiesel. New correlation coefficients for estimating the discharge coefficient and the spray angle are presented for cold conditions. Highlights: The properties of biodiesel and biodiesel blends were tested in cold conditions. The discharge coefficients of biodiesel and biodiesel blends in cold conditions were investigated. The spray penetration and spray angle of biodiesel and biodiesel blends in cold conditions were investigated.